Development of a Real-Time PCR Assay for Detection of Toxoplasma gondii in Pig and Mouse Tissues - Jauregui, L. H. (American Society for Microbiology, 2001)
A highly sensitive and specific method has been developed to reproducibly detect and quantitate Toxoplasma gondii burden in animal tissue samples using T. gondii ITS1-derived primers and a fluorogenic probe via real-time PCR. Assay specificity was confirmed against a panel of DNA samples from T. gondii and other common protozoa as well as host animal tissue. This Toxo TaqMan assay was able to detect as little as 0.1 pg of T. gondii genomic DNA, which is equivalent to 1 T. gondii bradyzoite, and has a dynamic range of detection of from 100 ng to 100 fg of T. gondii DNA. Tissues from experimentally infected mice and pigs as well as bradyzoite-spiked pig muscle samples were used to test and standardize this technique. Positive signals were obtained with T. gondii parasite concentrations ranging from 4 to 3.7 × 10(5) parasites per g of spiked pig tissue, with excellent linearity (R(2) = 0.9776). All T. gondii-infected animals were correctly identified by this technique. Results indicate that this assay is applicable to swine carcasses and commercial pig products, is compatible with automation technology for potential slaughterhouse use, and will enable scientists to diagnose and quantitate T. gondii in animal tissues.